Physical development and physical preparedness monitoring of lyceum students of different ages - S.L. Popel; R.I. Faychak; I.G. Tcap; P.M. Bejga; Y.O. Lysenko; Z. Śliwiński (H.S. Skovoroda Kharkiv National Pedagogical University, 2021)
In recent years, the health situation in Ukraine has deteriorated. According to statistics, 50% of children have poor health, 75% of children under 14 have chronic diseases, only 10% of school graduates can be called healthy. The overall incidence of children under the age of 14 increased by 16%, at the age of 15-17 - by 18%. Against this background, the level of physical development of children decreases. The current regulation has updated the work on the implementation of monitoring studies in various fields of activity and at different levels, including in the field of physical culture and sports, in order to increase the efficiency of the process of physical education of schoolchildren. Monitoring the physical development of adolescents is a complex information-analytical and prognostically important system that includes monitoring of health and physical development and its assessment, along with analysis at the level of an individual or a social group to predict future health, both for an individual and for the entire group persons united on a territorial basis or the nature of their activities. Such monitoring helps prevent negative trends in physical development in children and adolescents. Purpose: to analyze the results of monitoring the physical development and physical preparedness of students of the Lyceum Materials and methods: The analysis of materials on this issue was carried out based on the results of the implementation of the national educational initiative "Our New School" in accordance with the plan for the modernization of general education [3], according to which in 2019-2020 in secondary schools of Ivano-Frankivsk, the physical development of schoolchildren and schoolgirls was monitored 100 lyceum students 11-17 years old were examined, who were divided into 2 groups according to their academic performance: 1 gr. consisted of 50 lyceum students (35 girls and 15 boys) with high academic performance (average score 4.75), in the composition of 2 gr. it included 50 lyceum students - "lagging behind" (average score 3.5) (25 girls and 25 boys). Results: monitoring showed that, regardless of the group, lyceum students have an average level of physical development (girls - 62.1%, boys - 57.8%). Only 13.8% of girls and 14.4% of boys have a high level of physical development. Almost a quarter of high school students (23.9% of girls and 27.5% of boys) have a low level of physical development, and there are almost 2 times more such students than lyceum students with a high level of physical development. Conclusion: Summarizing the above, it should be noted that when implementing the results of monitoring physical development, there are two main directions: 1. Correction of deviations identified during monitoring in the state of development of physical condition. 2. Using student monitoring as a basis for creating a sports selection system. Based on this, we can conclude that an important component and subject of monitoring is the physical health of lyceum students, mainly in educational institutions, which contributes to monitoring and management decisions on making adjustments to the educational process.